KNDy neuron as a gatekeeper of puberty onset. Issue 6 (June 2014) - Uenoyama, Yoshihisa; Tsukamura, Hiroko; Maeda, Kei‐ichiro
Abstract Hypothalamo–pituitary–gonadal axis has been recognized as a functional unit orchestrating reproductive performance in mammals. The mechanism governing puberty onset, however, is still one of the great mysteries of biology. The present article reviews previous studies over the last century, which gradually elucidated the brain mechanism controlling puberty onset in mammals along with the discovery of gonadotrophins and the gonadotrophin‐releasing hormone and the establishment of the concept for the hypothalamo–pituitary–gonadal axis. The discovery of kisspeptin and subsequent progress of neuroendocrinology in the last decade has resulted in much greater understanding of the way the brain governs puberty onset in mammals.